Family resilience and protective factors promote flourishing and school engagement among US children amid developmental disorder and adverse psychosocial exposure. Issue 2 (4th March 2021) - Uddin, Jalal; Ahmmad, Zobayer; Uddin, Helal; Tatch, Andrew
Abstract: Early life psychosocial adversities and developmental disorders are common among children in the United States. However, there is relatively little research on how family processes and neighborhood-level factors may promote well-being among children dually burdened with developmental disorders (DD) and adverse childhood experience (ACE). Using secondary analysis of the National Survey of Children's Health 2016–2018 ( N  = 56, 831), we examined the associations of family resilience and other protective factors with flourishing and school engagement among subgroups of children with dual exposure to DD and ACE. Results indicate that family resilience, family meals, and mother's mental health promote flourishing and school engagement amid varying levels of exposure to ACE and DD. Social interventions designed to improve family and neighborhood resources can protect child well-being amid multiple adversities.